The impact of the exercise on the social mentality of the Chinese people - Ji, Shuyu; Zhang, Kaiqi; Xu, Ludan; Wang, Xiaolin; Dong, Delong; Yang, Xiannan (Public Library of Science, 2024)
Objective Engaging in exercise not only encompasses its intrinsic attributes but also signifies its social dimensions. It reflects an underlying emotional tone and cumulative value attributed to exercise by individuals, forming a broad, macro-level socio-psychological relationship in alignment with the conceptual definition of societal mentality. The social mentality is an indicator of a nation’s governance capacity and mirrors the overall socio-psychological profile and needs of its citizens. This study, therefore, aims to investigate the influence of exercise, specifically through the lens of sports, on the sociall mentality of the Chinese population, encompassing aspects of social trust and social equity. Additionally, we explore the distinct mechanisms underlying differences in social class, generation disparities, and spatial dimensions. This inquiry aims to contribute to enhancing governance capabilities and societal stability. Method Data for this study was sourced from the 2023 China General Social Survey. We selected 20 variables and analyzed a sample of 6,746 individuals. We employed Ordinary Least Squares (OLS) multiple linear regression models to construct our analysis. Results The findings indicate that exercise has a positive influence on the social mentality of the Chinese population. A higher frequency of participation in sports correlates with a more advanced level of social mentality development. Notably, significant disparities exist between the macro-level and micro-level impacts of exercise, suggesting ample room for improvement. Social class, generational disparities, and spatial dimensions demonstrate substantial impact, each exhibiting unique characteristics depending on the specific research question. Furthermore, the weightings of social trust orientation and social equity orientation within the societal mentality dimensions exhibit variability and fluctuations. Conclusion When exploring the topic of social mentality, it is recommended to separately discuss the various dimensions it encompasses, thus providing a comprehensive, detailed, and precise portrayal of specific issues. To bolster the influence of exercise on the social mentality, as well as to enhance governance capabilities and societal stability, the following recommendations are proposed: (1) In-depth exploration of differences within social strata to optimize the mechanisms through which exercise influences the social mentality; (2) Balancing generational disparities to establish a solid foundation for the influence of exercise on the social mentality; (3) Recognizing spatial dimensions to harness the spatial dynamism of exercise in shaping the social mentality. © 2024 Ji et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.